Sistem Pendaratan Otomatis pada Quadcopter menggunakan Sliding Mode Controller - Zindhu Maulana Ahmad Putra; Alrijadjis Alrijadjis; Bambang Sumantri (Universitas Syiah Kuala, 2020)
A quadcopter has a very nonlinear system characteristic that is inﬂuenced by unexpected disturbances such as the inﬂuence of wind that reﬂected off the ground when taking off or landing. Therefore, a robust control strategy is needed to improve the quadcopter performance. In this study, the control strategy is used to resolve outdoor automatic landing problems in a stable manner using the Sliding Mode Control (SMC) algorithm. The quadcopter has six degrees of freedom (6-DoF) with only four independent inputs, this makes it impossible to control 6-DoF directly and simultaneously. To handle this, the proposed structure is a multilevel control structure, inner loop dan outer loop controller. The Inner loop controls the rotational dynamics subsystem (3-DoF), while the outer loop controls the translational dynamics subsystem (3-DoF) which is designed in conjunction with the generation of attitude angle set-point. With the concept of automatics landing can reduce the risk of accidents on a quadcopter. The SMC technique on an automatics quadcopter landing shows the results with an error in roll of ± 0.05 radians, pitch ± 0.03 radians, yaw less than 0.3 radians, and translational movements the z-axis is ± 0.2 meters.